Teori Organisasi: Kekuasaan dan Politik - Taufiq, Muhammad; Yunita, Patria (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the central role of power and politics as dynamics that are inseparable from modern organisational life. The focus of the study is on how informal power is formed, how political behaviour influences decision-making processes, and its implications for organisational ethics and effectiveness. The method used is a systematic literature review of contemporary studies and thoughts on organisational power and politics that developed in the period 2020–2024. The results of the study show that power in modern organisations no longer stems solely from structural positions, but from the ability to control information, build narratives, manage relationships, and deal with uncertainty. Organisational politics functions as a mechanism for distributing resources, managing conflicts of interest, and responding to complex environmental dynamics. These findings confirm that organisations need to be understood as dynamic political arenas, requiring managers to possess political intelligence in order to manage influence and power effectively and ethically